Banking system, Institutional quality, and Economic growth: Panel data analysis on a sample of countries in the MENA region - Jamel, Lamia (Yayasan Ahmar Cendekia Indonesia, 2021)
The nexus among financial development and economic growth has long remained a subject matter of considerable debate in the financial and economic literature. This article examines the relationships between financial development, institutions, and economic growth. This indicates that the marginal effect of financial development on economic growth depends on the quality of institutions. To do so, we employ a panel data of 14 MENA countries during the period of study from 2008 to 2019. For the econometric methodology, we use fixed and random effects models. To choose between fixed effects and random effects, we employ the Hausman test. Based on the empirical findings, we demonstrate that financial development has a positive effect on economic growth. Furthermore, we have observed that institutional quality seems to be a necessary complement to financial development. Consequently, it is important to implement policies leading to the deepening of financial systems, through a including a solid institutional framework. Thus, by promoting such development and better institutional quality, economic growth will thus be accelerated.